Adherence to guideline of venous thromboembolism prophylaxis in a level 1 Trauma center in Thailand - Osaree Akaraborworn; Burapat Sangthong; Komet Thongkhao; Prattana Chainiramol; Khanitta Kaewsaengrueang (Archives of Trauma Research, 2018)
Objective: Venous thromboembolism (VTE) which includes deep vein thrombosis (DVT) and pulmonary embolism is a preventable complication in hospitalized trauma patients. Currently, the VTE guideline is the standard of care. However, underutilization of the guideline was reported. This study aimed to report the adherence to the VTE guideline in a Level 1 trauma center in Thailand. Methods: A retrospective review was performed on adult trauma patients admitted between January and December 2013. The inclusion criteria were Injury Severity Score ≥9 and admission in the hospital ≥7 days. The patients were classified into “very high risk of DVT,” “high risk of DVT,” and “high risk of bleeding” groups according to the hospital guideline. Adherence to the guideline, utility of the prophylaxis, and VTE occurrence were recorded. Results: During a 12-month period, 352 cases met the inclusion criteria. The overall adherence to the guideline was 28.9%, 5.2% in the “very high risk of DVT” group, 18.4% in the “high risk of DVT” group, and 57.9% in the “high risk of bleeding” group. VTE occurrence was 11 incidences in 10 patients (2.8%). The “high risk of bleeding” group had the highest in VTE occurrence (10 of 11 incidences). Conclusions: The adherence to the VTE prophylaxis guideline in Thailand was higher than previous studies. The pharmacological prophylaxis should be initiated as soon as possible.